2017
DOI: 10.1590/0103-6513.220916
|View full text |Cite
|
Sign up to set email alerts
|

Risk management for companies focused on innovation processes

Abstract: Risk is inherent to the activities of technology and innovation companies and to manage them represent an opportunity to improve the company capability to achieve its goals. The use of ERM models has been studied since the Committee of Sponsoring Organizations of the Treadway Commission guides. This article adapted the MIGGRI model for the context of an innovation company from a TSP in Brazil. Using a case study and a review from previous ERM literature, the article show that is possible to measure the risks t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
6
0
1
Order By: Relevance
“…This study further examined the impact of ERM on BMI and found significant positive results that supported H3. This is in line with Etges et al (2017) who reported that there is a benefit to implementing risk management practices in the strategic performance model of innovative organizations. However, numerous companies are still choosing to apply any risk management in the BMI process (Taran et al 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study further examined the impact of ERM on BMI and found significant positive results that supported H3. This is in line with Etges et al (2017) who reported that there is a benefit to implementing risk management practices in the strategic performance model of innovative organizations. However, numerous companies are still choosing to apply any risk management in the BMI process (Taran et al 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Besides, the implementation of risk management through the innovation process decreases the risks linked to the uncertainty and density of developing and implementing a new business model (Taran et al 2013). Therefore, there is a benefit to implement risk management practices in a strategic performance model for innovative organizations (Etges et al 2017). BMI needs heavy investment and has a high level of uncertainty, complexity, unavoidably and risk.…”
Section: Erm and Bmimentioning
confidence: 99%
“…If the implementation of autonomous ships does not bring sufficient economic benefits, shipping companies most likely will not be interested in investing in such solutions due to the low ROI (Return On Investment). Innovative solutions are usually associated with a greater uncertainty concerning their outcome, thus, implying higher risks and a need for managing the latter [14], especially in the low-margin shipping industry [15].…”
Section: Fully Autonomous Shipmentioning
confidence: 99%
“…There are also practical methods for managing project risks. In particular, the enterprise risk management (ERM) concept (Committee of Sponsoring Organizations of the Treadway Commission, 2007) is widely used to identify all the risks a company is exposed to (Etges, 2017). Similarly, ISO 31000 focuses on structuring the risk management process (International Organization for Standardization, 2009).…”
Section: Volmentioning
confidence: 99%